Beef cattle mineral nutrition in the Brazilian Pantanal. IV. Micronutrient survey on the lower Piquiri river - Pott, Edison S.; Brum, Paulo A. R. de; Pott, Arnildo; Almeida, Irajá L. de; Filho, José A. Comastri; Tullio, Rymer R. (Pesquisa Agropecuaria Brasileira, 2014)
Cu, Fe, Mn and Zn were analysed in samples of soil, forages and lactating zebu cows' liver from the lower Piqui, in the Brazilian Pantanal. Soils and forages were collected in "campo cerrado" or savanna grassland, "campo limpo" or open grassland, "cerrado"/woodland forest, in August and November 1981, and liver in these occasions plus March and May 1952. Average levels of Cu, Fe, Mn and Zn in Soil were 2 ppm, 496 ppm, 33 ppm and 3 ppm, respectively; and in forages, 5.9 ppm, 130 ppm, 224 ppm and 14 ppm respectively. Liver Fe levels varied from 516 ppm in August to 733 ppm in May, Cu from 129 ppm in November to 278 ppm in February; Mn from 29 ppm in November to 43 ppm in May, and Zn from 75 ppm in August to 153 ppm in November. In August, 65% of liver samples presented less than 80 ppm of Zn and in Novembor 37% less than 100 ppm of Cu. The results suggest the possibility of ocurrence of Zn deficiencies, mainly in the dry season, and Cu deficiencies, especially in the early rainy season.